Restringere lo spazio/semiotizzare il pianeta. Per una "macro-teoria del genere" e verso una tassonomia della "spy story" (Comparatismi, 2025)
A macro-theory of the spy story highlights the genre’s characteristics: 1) involvement in the plots of the entire world, which, however, undergoes a narrowing according to content-related or chronotopic dynamics; 2) a hyper-coding of elements of reality; and a consequent 3) paranoia as a form of constant and widespread fear. It is in light of this that we can develop a taxonomy of the spy story and, ultimately, highlight the decisive role of Thomas Pynchon’s literature.
Keywords: Spy; Space; Grahame Greene; John Le Carré; Thomas Pynchon